The Significance of Troponin and Ck-Mb in Association with Q-Wave Myocardial Infarction - Harahap, Urip; Margata, Linda (Talenta Publisher, 2018)
Abstract. Acute myocardial infarction (AMI) is the global main cause of morbidity and mortality. AMI describes the process of cell death due to prolonged ischemia identified by the appearance of pathological Q-wave in electrocardiogram (ECG). Myocardial cell death does not occur directly after the onset of myocardial ischemia, however, it occurs more than 6 hours after the onset. Thus, certain cardiac markers, such as cardiac troponin and creatinine kinase-MB (CK-MB) which formed in myocardial cell damage, play a vital role in diagnosing AMI. Keywords: Cardiac Biomarker, CK-MB, Diagnosis, Q-wave Myocardial Infarction, Troponin